PENGARUH PERSEPSI TENTANG PROFESI GURU TERHADAP MINAT MENJADI GURU PADA MAHASISWA STKIP PESISIR SELATAN - Veni Veni (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2022)
This study aims to determine the influence of perceptions about the teaching profession on interest in becoming a teacher in the students of STKIP Pesisir Selatan students. This research is quantitative descriptive. The population in this study was 31 students of STKIP Pesisir Selatan who had implemented PLK. Data were collected through a questionnaire/questionnaire and analyzed using the Statistical Product and Service Solution (IBM SPSS Statistic 22) program. The results showed that there was an influence of perceptions about the teaching profession on interest in becoming a teacher by students of STKIP Pesisir Selatan by 23.3% and 76.7% influenced by other variables outside this study.